Burden of atrial fibrillation and its attributable risk factors from 1990 to 2019: An analysis of the Global Burden of Disease study 2019 - Xu, Shangbo; Chen, Yangbo; Lin, Rui; Huang, Weipeng; Zhou, Haoyue; Lin, Yongjian; Xu, Mingwei (Frontiers in Cardiovascular Medicine, 2022)
Background: Understanding the pattern and trend of the atrial fibrillation (AF) burden are essential for developing effective preventive strategies. The purpose of this study was to estimate AF burdens and risk factors in 204 countries and territories between 1990 and 2019. Methods: Data were extracted from the Global Burden of Disease 2019, including incidence, death, disability-adjusted life-years (DALYs), and the attributable risk factors. In order to quantify changes in the age-standardized incidence rate (ASIR), age-standardized death rate (ASDR), and age-standardized DALY rate between 1990 and 2019, the estimated annual percentage change (EAPC) was used. Also, AF burden was assessed in relation to the Socio-demographic Index (SDI). Results: Globally, there were 4,720,324 incident cases, 117,038 deaths and 8,393,635 DALYs in 2019. There were no significant changes in ASIR, ASDR, or age-standardized DALY rates from 1990 to 2019. Although the burden and trend of AF varied in different regions and countries, the ASIR, ASDR and age-standardized DALY rate were positively correlated with SDI. Furthermore, the burden of AF was higher in males and elderly. The age-standardized DALY rate worldwide was primarily attributable to high systolic blood pressure, followed by high body-mass index, alcohol use, smoking, diet high in sodium and lead exposure. Conclusions: AF remained a major public health challenge worldwide, with substantial variation at regional and national levels. There is an urgent need to increase public awareness about AF risk factors and to bring about cost-effective interventions for AF in order to reduce its future burden.